Slipping up on the sliding scale: fluid and electrolyte management in variable rate intravenous insulin infusions. (June 2016) - Rickard, LJ; Cubas, V; Ward, ST; Hanif, W; Suggett, E; Ismail, T; Ghosh, S
Abstract: This study aimed to analyse variations in intravenous fluid therapy and electrolyte management with variable rate intravenous insulin infusions (VRIIIs); and to quantify serum electrolyte changes pre‐ versus post‐VRIII and variations therein depending on supplemented fluid electrolyte compositions. A retrospective study was undertaken involving 174 VRIIIs prescribed over a 10‐week period at a tertiary teaching hospital. Each VRIII had their associated fluid prescription and serum electrolytes analysed. The results showed that 5% dextrose (46%) and 0.9% NaCl (34%) were the most commonly prescribed fluids; 64% of fluids did not have the recommended potassium supplementation. Administration of a VRIII resulted in a significant drop in serum potassium levels (p < 0.0001) for those who did not receive supplementation. There was no drop in serum potassium for those patients who did receive supplemental potassium. Eleven patients (6.4%) developed new‐onset hypokalaemia (K ≤3.5 mmol/L) after implementation of a VRIII. Our study supports the hypothesis that VRIIIs cause hypokalaemia and that this can be averted by supplemental potassium, thus preventing potentially avoidable hypokalaemic complications. A large variation exists in prescribing fluids with VRIIIs. Introduction of the national surgical and medical VRIII guidelines, together with improved availability to recommended fluids, and a quality improvement project, are our next steps to improve patient outcomes. Copyright © 2016 John Wiley & Sons.